ALBUMIN VERSUS STANDARD MEDICAL TREATMENT IN BRAZILIAN PUBLIC AND PRIVATE HEALTHCARE SYSTEMS - Carlos TERRA; Elisabet VIAYNA; Laura AYZIN; Cristina FUSTER; Susana ACEITUNO; Claudio TAFLA (Arquivos de Gastroenterologia, 2023)
ABSTRACT Background: Cirrhosis is one of the final stages of chronic liver disease. Common causes of cirrhosis include alcoholism and viral hepatitis infections. Cirrhosis can progress from an asymptomatic, compensated phase to decompensation and the appearance of overt symptoms. There is no specific treatment for decompensated cirrhosis. The ANSWER trial positioned long-term albumin infusions as a potential treatment for patients with cirrhosis and uncomplicated ascites. Objective: This study assesses the economic impact of albumin infusions following the ANSWER trial regimen in Brazilian patients with decompensated cirrhosis from the public and private healthcare systems perspectives. Methods: The incremental cost per patient per year was calculated for standard medical treatment (SMT) plus long-term albumin infusions versus SMT alone. Costs of diuretics and albumin were obtained from Banco de Preços em Saúde and the Drug Market Regulation Chamber. Costs for complication and procedures were gathered from the published literature. Costs were transformed to 2021 Brazilian reals (BRL). Incidences of clinical complications and treatments were gathered from the ANSWER trial. Univariate sensitivity analysis was performed by increasing and decreasing all inputs by 20%. Results: The cost per patient per year was 118,759 BRL and 189,675 BRL lower for patients treated with SMT and albumin (compared to SMT only) for the public and private healthcare systems, respectively. The additional cost of albumin was offset by reduced complications and treatments (149,526 BRL and 249,572 BRL, respectively). The univariate sensitivity analysis showed cost savings for both healthcare systems in all the scenarios assessed. Conclusion: This economic analysis suggests that, if the ANSWER trial clinical outcomes translate into real-world effectiveness, addition of albumin infusions to SMT in patients with decompensated cirrhosis may lead to cost savings for the public and private healthcare systems in Brazil.